Bruceine D inhibits Cell Proliferation Through Downregulating LINC01667/MicroRNA-138-5p/Cyclin E1 Axis in Gastric Cancer - Li, Lin; Dong, Zhen; Shi, Pengfei; Tan, Li; Xu, Jie; Huang, Pan; Wang, Zhongze; Cui, Hongjuan; Yang, Liqun (Frontiers in Pharmacology, 2020)
Objective: Gastric cancer is one of the most common malignant tumors. Bruceine D (BD) is one of the extracts of Brucea javanica. In recent years, it has been reported that BD has anti-tumor activity in some human cancers through different mechanisms. Here, this study try to explore the effect of BD on gastric cancer and its regulatory mechanism. Methods: Cell proliferation ability was detected by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assays, 5-bromo-2-deoxyuridine (BrdU) staining and soft agar colony formation assay, respectively. The tumor xenograft model was used to verify the effect of BD on the tumorigenicity of gastric cancer cells in vivo. Flow cytometry analysis and Western blot assay were performed to detect cell cycle and apoptosis. Gastric cancer cells were analyzed by transcriptome sequencing. The interaction between LINC01667, miR-138-5p and Cyclin E1 was verified by dual luciferase experiment and RT-PCR assays. Results: We found that BD significantly inhibited cell proliferation and induced cell cycle arrest at S phase in gastric cancer cells. Transcriptome analysis found that the expression of a long non-coding RNA, LINC01667, were significantly down-regulated after BD treatment. Mechanically, it was discovered that LINC01667 upregulated the expression of Cyclin E1 by sponging microRNA-138-5p (miR-138-5p). Furthermore, BD enhanced the chemosensitivity of gastric cancer cells to doxorubicin, a clinically used anti-cancer agents. Conclusions: BD inhibit the growth of gastric cancer cells by downregulating the LINC01667/miR-138-5p/Cyclin E1 axis. In addition, BD enhances the chemosensitivity of gastric cancer cells to doxorubicin. This study indicate that BD may be used as a candidate drug for the treatment of patients with gastric cancer.